Self-Assembly of Pseudo Isocyanine Chloride in the Presence of Attractive Polyethylene Glycol Crowders - Koch, Leon; Rajput, Satyendra; Richter, Antonio; König, Benedikt; Nayar, Divya; Ebbinghaus, Simon; Huber, Klaus (The Journal of Physical Chemistry B)

Disaggregation at High Volume Exclusion: An “Overcrowding” Effect - Koch, Leon; Baier, Dominik; Rajput, Satyendra; König, Benedikt; Tiemann, Michael; Ebbinghaus, Simon; Nayar, Divya; Huber, Klaus (The Journal of Physical Chemistry B)

Water-in-Salt LiTFSI Aqueous Electrolytes. 1. Liquid Structure from Combined Molecular Dynamics Simulation and Experimental Studies - Zhang, Yong; Lewis, Nicholas H. C.; Mars, Julian; Wan, Gang; Weadock, Nicholas J.; Takacs, Christopher J.; Lukatskaya, Maria R.; Steinrück, Hans-Georg; Toney, Michael F.; Tokmakoff, Andrei; Maginn, Edward J. (The Journal of Physical Chemistry B)

Midinfrared Birefringence of Liquid Crystals, Polarimetry, and Intensity Modulators - Atorf, Bernhard; Auf der Landwehr, Chris Holm; Rennerich, Roman; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry B)

Ferroelectric Liquid Crystals in Microcapillaries: Observation of Different Electro-optic Switching Mechanisms - Knust, Steffen; Wahle, Markus; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

Influence of Proton and Salt Concentration on the Chromonic Liquid Crystal Phase Diagram of Disodium Cromoglycate Solutions: Prospects and Limitations of a Host for DNA Nanostructures - Zhang, Bingru; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

Temperature-Dependent Hole Mobility and Its Limit in Crystal-Phase P3HT Calculated from First Principles - Lücke, Andreas; Ortmann, Frank; Panhans, Michel; Sanna, Simone; Rauls, Eva; Gerstmann, Uwe; Schmidt, Wolf Gero (The Journal of Physical Chemistry B)

Structure and Dynamics of the Instantaneous Water/Vapor Interface Revisited by Path-Integral and Ab Initio Molecular Dynamics Simulations - Kessler, Jan; Elgabarty, Hossam; Spura, Thomas; Karhan, Kristof; Partovi-Azar, Pouya; Hassanali, Ali A.; Kühne, Thomas D. (The Journal of Physical Chemistry B)

Structure and Dynamics of the Instantaneous Water/Vapor Interface Revisited by Path-Integral and Ab Initio Molecular Dynamics Simulations - Kessler, Jan; Elgabarty, Hossam; Spura, Thomas; Karhan, Kristof; Partovi-Azar, Pouya; Hassanali, Ali A.; Kühne, Thomas (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

Influence of Structural Defects and Oxidation onto Hole Conductivity in P3HT - Lücke, A.; Schmidt, Wolf Gero; Rauls, E.; Ortmann, F.; Gerstmann, Uwe (The Journal of Physical Chemistry B)

Coaggregation of Two Anionic Azo Dyestuffs: A Combined Static Light Scattering and Small-Angle X-ray Scattering Study - Michels, Rolf; Goerigk, Günter; Vainio, Ulla; Gummel, Jérémie; Huber, Klaus (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

Kinetic and Structural Features of a Dyestuff Coaggregation Studied by Time-Resolved Static Light Scattering - Michels, Rolf; Hertle, Yvonne; Hellweg, Thomas; Huber, Klaus (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

Co-Aggregation of Two Anionic Azo Dyestuffs at a Well-Defined Stoichiometry - Michels, Rolf; Sinemus, Thomas; Hoffmann, Jan; Brutschy, Bernhard; Huber, Klaus (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

Doping a Mixture of Two Smectogenic Liquid Crystals with Barium Titanate Nanoparticles - Lorenz, Alexander; Zimmermann, Natalie; Kumar, Satyendra; Evans, Dean R.; Cook, Gary; Fernández Martínez, Manuel; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

Spectral Signatures of Polarons in Conjugated Co-polymers - Wiebeler, Christian; Tautz, Raphael; Feldmann, Jochen; von Hauff, Elizabeth; Da Como, Enrico; Schumacher, Stefan (The Journal of Physical Chemistry B)

Solvation of Small Disulfonate Anions in Water/Methanol Mixtures Characterized by High-Field Pulse Electron Nuclear Double Resonance and Molecular Dynamics Simulations - Heller, Jeannine; Elgabarty, Hossam; Zhuang, Bilin; Sebastiani, Daniel; Hinderberger, Dariush (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

The Amplitude Reduction Factor and the Cumulant Expansion Method: Crucial Factors in the Structural Analysis of Alkoxide Precursors in Solution - Bauer, Matthias; Bertagnolli, Helmut (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

Temperature-Induced Collapse of Alkaline Earth Cation−Polyacrylate Anion Complexes - Lages, Sebastian; Schweins, Ralf; Huber, Klaus (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

Early Stages of ZnS Growth Studied by Stopped-Flow UV Absorption Spectroscopy: Effects of Educt Concentrations on the Nanoparticle Formation - Tiemann, Michael; Marlow, Frank; Brieler, Felix; Lindén, Mika (The Journal of Physical Chemistry B)
The growth of ZnS nanoparticles by precipitation from supersaturated aqueous solution is studied by stopped-flow UV absorption spectroscopy. The average size, size distribution, and concentration of the particles are monitored within the sub-second time regime with a resolution of 1.28 ms. Particle growth at these early stages is governed by pronounced ripening. The UV absorption data strongly suggest that growth occurs by preferential adsorption of HS- anions relative to Zn2+ or ZnOH+ cations. Correspondingly, the initial sulfide concentration has a much more pronounced influence on the growth kinetics than the initial zinc concentration. These findings are verified by ζ-potential measurements which confirm that the particle surfaces are negatively charged under near-neutral pH conditions.

Initial Stage of Si(001) Surface Oxidation from First-Principles Calculations - Fuchs, F.; Schmidt, Wolf Gero; Bechstedt, F. (The Journal of Physical Chemistry B)